Development and validation of a minimally invasive protocol for assessing oxidative stress markers in exfoliated oral cells - de Abreu, Lukas Mendes [UNESP]; da Silva, Cintia Rodrigues [UNESP]; Bortoleto, Ana Laura Ferreira [UNESP]; Nunes, Giovana Barros [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Wiley, 2024)
Objectives: This study aimed to develop and validate a minimally invasive protocol for characterizing oxidative stress markers in exfoliated oral cells. Materials and Methods: Exfoliated oral cells were collected from healthy volunteers. The protocol included the utilization of specific fluorescent probes to measure intracellular reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm) and reduced glutathione (GSH). Cells from each volunteer were divided into the positive and negative control groups, which were, respectively, exposed or not to hydrogen peroxide (H2O2) aiming to induce the oxidative stress. Measurements of cell fluorescence were performed using a microscope equipped with epifluorescence. Results: The results showed that cells exposed to H2O2 exhibited significantly higher intracellular expression of ROS compared to unexposed cells (positive control: 3851.25 ± 1227.0 vs, negative control: 1106.07 ± 249.6; p = 0.0338). On the contrary, cells exposed to H2O2 displayed decreased expression of ΔΨm (p = 0.0226) and GSH (p = 0.0289) when compared to the negative control group (ΔΨm positive control: 14634.39 ± 1529.0 vs, negative control: 18897.60 ± 2338.0; and GSH positive control: 9011.08 ± 1900.0 vs, negative control: 15901.79 ± 2745.0). Conclusions: The developed protocol proved to be effective in detecting and quantifying oxidative stress biomarkers, such as ROS, ΔΨm and GSH, in exfoliated oral cells. This minimally invasive approach offers a promising method to assess oxidative stress expression and may be clinically relevant in the evaluation of oral diseases associated with oxidative stress.
Keywords: biomarkers; buccal mucosal cells; fluorescent probe; oxidative stress